PENINGKATAN KESADARAN MASYARAKAT TERHADAP RISIKO TERJADINYA INFEKSI OTAK AKIBAT HIV - Sensusiati, Anggraini (Universitas Negeri Surabaya, 2024)
The high number of HIV cases in Surabaya City is a big task for the government, stakeholders, and all levels of society. Public ignorance of the risk of brain infection in people with HIV/AIDS needs attention from health workers and health educators. Therefore, the community service team of the Faculty of Medicine UNAIR in collaboration with the Surabaya City Health Office and Kalijudan Community Health Center held socialization and training for HIV cadres as an effort to increase public awareness of the risk of brain infection due to HIV. The writing of this article aims to provide an overview of the implementation of socialization and training of HIV cadres. The activity aimed to increase cadre knowledge related to HIV and cerebral toxoplasmosis and effective communication training practices. The methods used to implement these activities are educational video screenings, lectures, questions and answers, and hands-on practice. The results showed that 80% of cadres experienced an increase in knowledge.